2013
DOI: 10.1039/c2dt32095a
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic rhodium NHC complexes with pyridine-derived ligands: synthetic accessibility and reactivity towards oxygen

Abstract: The synthesis, structure determination and oxidative stability of novel Rh-NHC complexes which feature pyridine-derived ligands have been described. All complexes described herein were synthesized from common dinuclear precursors of general structure [Rh(NHC)(L)Cl](2), where L is a monodentate olefin. We demonstrate that the use of these precursors is critical for the formation of all complexes since related cyclooctadiene containing precursors ([Rh(NHC)(COD)Cl]) were completely unreactive under identical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 81 publications
(154 reference statements)
1
7
0
Order By: Relevance
“…The observed chemical shifts and coupling constants for the carbene resonance are similar to those that have been reported previously for square planar Rh(I) complexes with NHC ligands. 20,23,24,26,[28][29][30][31] For each complex, the positive electrospray mass spectrum obtained contained the parent ions corresponding to the entire cationic metal complex with one NHC-1,2,3-triazolyl ligand and one COD co-ligand. This suggests that the NHCtriazolyl ligands coordinate to the Rh(I) centre in a bidentate fashion and together with the COD co-ligands form the expected square planar Rh(I) complexes.…”
Section: Dalton Transactionsmentioning
confidence: 99%
“…The observed chemical shifts and coupling constants for the carbene resonance are similar to those that have been reported previously for square planar Rh(I) complexes with NHC ligands. 20,23,24,26,[28][29][30][31] For each complex, the positive electrospray mass spectrum obtained contained the parent ions corresponding to the entire cationic metal complex with one NHC-1,2,3-triazolyl ligand and one COD co-ligand. This suggests that the NHCtriazolyl ligands coordinate to the Rh(I) centre in a bidentate fashion and together with the COD co-ligands form the expected square planar Rh(I) complexes.…”
Section: Dalton Transactionsmentioning
confidence: 99%
“…On the basis of this fact, our research group has developed in recent years a variety of NHC-based rhodium catalysts active in C–H activation . Particularly, dinuclear compounds with the general formula [Rh­(μ-Cl)­(NHC)­(η 2 - olefin)] 2 proved to be valuable starting materials for the preparation of mononuclear complexes RhCl­(NHC)­(η 2 - olefin)­(L) by simple bridge cleavage with a nucleophilic ligand . These derivatives exhibited excellent activities and selectivities in catalytic alkyne homo- and cross-dimerization, as well as hydroalkenylation of N -vinylpyrazoles, 2-thienylpyridine, and 2-vinylazines , to produce valuable N-bridge heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…23 In particular, NHC complexes of Rh and other transition metals can undergo cleavage of the metal-carbon bond of the NHC under remarkably mild conditions. 16,[24][25][26][27][28][29] In addition, we have also demonstrated that Rh-NHC complexes can react rapidly with oxygen, in some cases providing Rh-O 2 complexes with highly unusual bonding modes (Fig. 1).…”
Section: Introductionmentioning
confidence: 60%
“…As expected, complexes 5 and 6, which instead contain saturated NHCs, display resonances that are even further downshifted at >200 ppm. 35,69 In contrast to this, Rh III NHC complexes generally exhibit a significant upfield shift of the carbene resonance (Δ ∼ 20 ppm) seemingly regardless of the nature of the ancillary ligands, 29,[70][71][72] or the nature of the carbene itself. 73 We observed this upfield shift in cationic complexes 7 and octahedral P-N chelate complexes 9 and 10 (Table 2).…”
Section: Nmr Spectroscopymentioning
confidence: 91%
See 1 more Smart Citation